Pressure effect on Si quantum-dot potential - Yarub K. A., Al-Douri; Uda, Hashim, Prof. Dr.; Ahmed, N. M.; Zaliman, Sauli, Prof. Madya (American Institute of Physics, 2010)
Link to publisher's homepage at http://scitation.aip.org/